EXPLORING THE EFFECTS OF GENDER AND PROFICIENCY LEVELS ON TURKISH EFL LEARNERS' BELIEFS ABOUT LANGUAGE LEARNING: A CROSS-SECTIONAL STUDY - Fatma Zehra Özkahya (Informascope, 2017)
Language learners' beliefs about second language learning interact with their awareness, consciousness, attitude towards learning, strategy choices and motivations (Buyukyazi, 2010). Delving into learners' beliefs provides an insightful view of learners' perceptions and actions about their education, which also helps teachers to shape the language learning process with changing or adapting the methods and materials thereby reshaping the negative preconceptions of the learners about English language. To see the effect of the learners' gender and language proficiency levels, 43 university level students contributed to the study. The data were collected with a 34-item Likert Scale called as The Beliefs about Language Learning Inventory (BALLI) developed by Horwitz. The data analysis revealed that while learners' gender has no significant effect on the learners' belief, their proficiency levels affect their beliefs about the nature of the language, foreign language aptitude, motivations and expectations from their second language learning procedures. Keywords: language learner's belief; attitude; aptitude; preconception